PENGARUH BRAND IMAGE DAN STORE IMAGE TERHADAP KEPUTUSAN PEMBELIAN KFC MERR SURABAYA - Jayanti, Eka; Wardani, Nuruni Ika Kusuma (JURNAL LENTERA BISNIS, 2026)
The global fast-food market continues to grow. The fast-food industry is projected to grow at a CAGR of 7% annually. This growth presents significant business opportunities for players in the fast-food sector, particularly fast-food restaurants. Fast-food entrepreneurs will increasingly innovate to influence consumers to purchase their products. This study aims to determine the influence of brand image and store image on purchasing decisions for KFC MERR Surabaya. Data collection for this study was conducted by distributing an online questionnaire to 140 respondents who are KFC MERR Surabaya customers and reside in Surabaya. The sampling technique used was non-probability sampling with a purposive sampling method. The data analysis method used was Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of this study indicate that the variables Brand Image and Store Image have a significant influence on the purchase decision for KFC MERR Surabaya products. These findings suggest that a positive image can drive increased sales and boost revenue for KFC MERR Surabaya